Peculiarities of the weed infestation of young paulownia (Paulownia tomentosa L.) stands - Nychkaliuk, H. (Quarantine and plant protection, 2023)
Goal. To study the weeding processes of young Paulownia tomentosa (Paulownia tomentosa L.) plantations for the further development of an effective weed protection system in the conditions of the Forest Steppe of Ukraine. Methods. To study the interaction of research objects with weather conditions, cultivation methods and technology, field methods (in particular, small-plot), as well as visual, measuring, weight, quantitative and physiological methods were used. The laboratory method was used to determine the quality characteristics of the soil of the experimental plots. Processing of experimental data was performed using the Microsoft Office Excel computer program. Results. It was established that young stands of paulownia in the first stages of vegetation are actually a free ecological niche, which is quickly filled by weeds. The largest number of weed species was from the Gramineae, Brassicaceae, and Asteraceae families. There was one species each from the Polygonaceae, Chenopodiaceae, Solanaceae, and Convolvulaceae families. In the second year of vegetation, the seedlings of Echinochloa crusgalli (L. Pal. Beauv), Chenopodium album L., Elymus repens (L.) Gould, Setaria glauca (L.) Pal. Beauv, Sinapis arvensis L., Polygonum convolvulus L., Thlaspi arvense L. On average, more weed seedlings were recorded during the accounting period than in the first year of crop vegetation. Conclusions. It has been experimentally proven that before establishing the plantations, the site should be evaluated for the presence of problematic weed species that can potentially multiply in paulownia plantations and interfere with effective plant care. The presence of weeds in young paulownia stands during the growing season leads to a significant suppression of culture plants. Establishing the features of the formation of weeding of paulownia plantations in the second year of vegetation is impossible without a comprehensive determination of plant growth parameters. Information about the specifics of weeding make it possible to correctly develop an effective system of protection against weeds.